Neither housing nor hotel: The emergence of “medium-term rentals” in post-Covid Canadian cities - Wachsmuth, David; Buglioni, Bridget (Canadian Planning and Policy / Aménagement et politique au Canada, 2024)
One of the many impacts of the Covid pandemic on Canadian cities was the complete collapse of short-term rental (STR) markets, as long-distance travel nearly vanished for more than a year. Many dedicated STRs shifted back to the long-term rental market, but others remained on STR platforms such as Airbnb but with minimum stays of one month or more—a land use we describe as “medium-term rentals” (MTRs). This paper provides a planning analysis of online-platform-mediated MTRs in Canadian cities and their housing-market, land-use, and regulatory implications. First, we identify and explore the regulatory grey zone inhabited by MTRs, which appear to be neither standard residential tenancies nor short-term tourist accommodations. Second, the paper provides a brief empirical overview of the emergence of MTRs during and after the Covid pandemic in Toronto, Montreal, and Vancouver. Third, the paper uses a policy case study of situations in which Ontario’s Landlord and Tenant Board has been asked to adjudicate non-standard tenancies to establish whether there is a planning basis for distinguishing medium-term rentals from other tenancy types. The paper concludes by identifying a key planning principle which could allow Canadian municipalities to pull MTRs out of the regulatory grey zone: regulating type of stay instead of length of stay.